2020
DOI: 10.1007/s10651-020-00445-5
|View full text |Cite
|
Sign up to set email alerts
|

Generalised Additive Models and Random Forest Approach as effective methods for predictive species density and functional species richness

Abstract: Species distribution modelling (SDM) is a family of statistical methods where species occurrence/density/richness are combined with environmental predictors to create predictive spatial models of species distribution. However, it often turns out that due to complex multi-level interactions between predictors and the response function, different types of models can detect different numbers of important predictors and also vary in their predictive ability. This is why we decided to explore differences in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 86 publications
(89 reference statements)
2
30
0
1
Order By: Relevance
“…Our results highlight a general different pattern among these tools, not only in the absolute biomass estimates but also in the temporal and spatial distribution. These two models are commonly used to assess species distributions in both marine and terrestrial realms (e.g., Moisen et al, 2006;Rooper et al, 2017;Kosicki, 2020), however RF models have been seen to have substantially more performance power and control over the model overfitting compared to GAM approaches (Elith et al, 2006;Rooper et al, 2017), as it is also shown in this study. This is likely because of the RF algorithm, which is an ensemble of models (regression trees), each built on a random selection of relatively few predictors (Breiman, 2001).…”
Section: Data Quality and Model Performancementioning
confidence: 59%
“…Our results highlight a general different pattern among these tools, not only in the absolute biomass estimates but also in the temporal and spatial distribution. These two models are commonly used to assess species distributions in both marine and terrestrial realms (e.g., Moisen et al, 2006;Rooper et al, 2017;Kosicki, 2020), however RF models have been seen to have substantially more performance power and control over the model overfitting compared to GAM approaches (Elith et al, 2006;Rooper et al, 2017), as it is also shown in this study. This is likely because of the RF algorithm, which is an ensemble of models (regression trees), each built on a random selection of relatively few predictors (Breiman, 2001).…”
Section: Data Quality and Model Performancementioning
confidence: 59%
“…The higher performance of RF is attributed to its ability to avoid overfitting as it combines and votes the most popular class from several individual trees (Breiman 2001). Due to its higher performance, it is the most flexible and widely applied machine learning algorithm for various field of studies such as land cover classification (Abdi 2020), forest monitoring (Ma et al 2020), species richness, and density (Kosicki 2020), and invasive species modelling (Ng et al 2018). In addition, its capability for remote sensing-based studies is also immense as it requires minimum time for satellite image classification (Sabat-Tomala et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Random Forest (RF) RF (Breiman 2001), a combination of tree predictors, is the most commonly used machine learning algorithm (Abdi 2020). It is an effective method for predicting species richness and density (Kosicki 2020).…”
Section: Short Description Examplesmentioning
confidence: 99%
“…Model‐based estimates were achieved by fitting a detection function (the probability of animal detection as a function of perpendicular distance) followed by fitting generalized additive models (GAMs; Wood et al, 2016) to explore the relationship of animal presence and abundance to environmental covariates. This relationship was then used to predict animal density in the study area limited by the range of observed environmental values fitted in the GAM (Franchini et al, 2020; Kosicki, 2020; Mannocci et al, 2014). In addition, standard distance sampling estimates were also calculated, which can be found in the Appendix .…”
Section: Methodsmentioning
confidence: 99%